A trajectory smoothing method at signalized intersection based on individualized variable speed limits with location optimization. (July 2018) - Yao, Handong; Cui, Jianxun; Li, Xiaopeng; Wang, Yu; An, Shi
Highlights: Propose the system of Individual Variable Speed Limits with Location Optimization (IVSL-LC). Consider regulation of vehicle trajectory shapes associated fuel consumption and traffic throughput. Determine not only configurations but also locations of individual advisory speeds. Focus on near-future connected vehicle technologies without automation capabilities. Consider compliance rates of human drivers. Abstract: Traffic signals on urban highways force vehicles to stop frequently and thus causes excessive travel delay, extra fuel consumption and emissions, and increased safety hazards. To address these issues, this paper proposes a trajectory smoothing method based on Individual Variable Speed Limits with Location Optimization (IVSL-LC) in coordination with pre-fixed traffic signals. This method dynamically imposes speed limits on some identified Target Controlled Vehicles (TCVs) with Vehicle to Infrastructures (V2I) communication ability at two IVSL points along an approaching lane. According to real-time traffic demand and signal timing information, the trajectories of each approaching vehicle are made to run smoothly without any full stop. Essentially, only TCVs' trajectories need to be controlled and the other vehicles just follow TCVs with Gipps' car-following model. The Dividing RECTangles (DIRECT) algorithm is used to optimize the locations of the IVSLs. Numerical simulation is conducted to compare the benchmark case without vehicle control, the individual advisory speed limits (IASL) and the proposed IVSL-LC. The result shows that compared with the benchmark, the IVSL-LC method can greatly increase traffic efficiency and reduce fuel consumption. Compared with IASL, IVSL-LC has better performance across all traffic demand levels, and the improvements are the most under high traffic demand. Finally, the results of compliance analysis show that the effect of IVSL-LC improves as the compliance rate increases.